(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Guduchi (Tinospora cordifolia (Willd.) Miers], Menispermaceae family, it is important medicinal plant is widely distributed through India. It is categorized as "Rasayana" and the whole plant is used medicinally. The aim of the present study is to evaluate the protective effect of Guduchi patra swaras against paracetamol induced liver damage in Wister albino rats. Material & Methods: Wistar Albino rats (140-250g) will be divided into 6 group and each group 6 rats, into control group, paracetamol control, standard group, test group. The test drug Guduchi patra swarasa was administered orally for 10 consecutive days and two dose of the toxicant (paracetamol) were administered orally to each group, on two alternate days i.e., 7th and 9th day, 1hr after test drug administration. After 48 hours of toxicant paracetamol, and standard group. The blood was collected in EDTA tube and sent for biochemistry laboratory for biochemical investigations. Result: The analysis of serum biochemical parameters shows that administration of paracetamol leads to significant change in majority of the parameters. The overall activity profile indicated reversal of important parameters like SGOT, SGPT, total bilirubin, total protein, blood sugar level, serum globulin, serum albumin, serum total cholesterol and serum triglycerides. All three test groups of Guduchi patra Swarasa administered are found to be effective heapto-protective especially based on histo-pathological study. Among the three groups, the double dose group and therapeutic group has shown good results in comparison with the other two groups. Conclusion: In the present study, the overall activity profile of Guduchi patra Swarasa administered are found to be effective hepatoprotective among the three groups therapeutic double dose shows good results in comparison with the other group.